1D thermoembolization model using CT imaging data for porcine liver - Rohan Amare; Danielle Stolley; Steve Parrish; Megan Jacobsen; Rick R. Layman; Chimamanda Santos; Beatrice Riviere; Natalie Fowlkes; David Fuentes; Erik Cressman (Scientific Reports)
Abstract Innovative therapies such as thermoembolization are expected to play an important role in improving care for patients with diseases such as hepatocellular carcinoma. Thermoembolization is a minimally invasive strategy that combines thermal ablation and embolization in a single procedure. This approach exploits an exothermic chemical reaction that occurs when an acid chloride is delivered via an endovascular route. However, comprehension of the complexities of the biophysics of thermoembolization is challenging. Mathematical models can aid in understanding such complex processes and assisting clinicians in making informed decisions. In this study, we used a Hagen-Poiseuille 1D blood flow model to predict the mass transport and possible embolization locations in a porcine hepatic artery. The 1D flow model was used on imaging data of in-vivo embolization imaging data of three pigs. The hydrolysis time constant of acid chloride chemical reaction was optimized for each pig, and leave-one-out-cross-validation (LOOCV) method was used to test the model’s predictive ability. This basic model provided a balanced accuracy rate of $${70.5}{%}$$ for identifying the possible locations of damage in the hepatic artery. Use of the 1D model and experimental data provides an insight that using immiscible two-phase flow would better approximate the globular behavior seen.